2017
DOI: 10.1002/cite.201600189
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomorphic Transformation of Porous Glasses into Micelle‐Templated Silica

Abstract: Micelle-templated silica (MTS)-composites with flexible macroscopic shape, monomodal or bimodal (hierarchical) pore structure, and high mechanical stability can be prepared by partial or complete pseudomorphic transformation of porous glasses (PG). The state of research concerning synthesis, transformation mechanism, characterization, and application of MTS/PG-composites is reviewed and the investigation of the transformation products by 129 Xe NMR spectroscopy and the direct synthesis of Al-MCM-41/PG-composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Instead of powdered samples, particles reflecting the macroscopic shape of the starting material are obtained. [ 98 ] For this process, two different mechanisms are possible: The transformation may proceed homogeneously from the outside to the inside of the particle or vice versa, or it may start in certain domains dispersed over the particle, and then spread. Matysik and co‐workers tried to answer this question for the transformation of a silica gel, LiChrospher, which possesses a broad pore size distribution between 10 and 50 nm, to the well‐ordered MCM‐41 exhibiting hexagonally arranged pores with a very narrow pore size distribution of ≈4 nm.…”
Section: Recent Applicationsmentioning
confidence: 99%
“…Instead of powdered samples, particles reflecting the macroscopic shape of the starting material are obtained. [ 98 ] For this process, two different mechanisms are possible: The transformation may proceed homogeneously from the outside to the inside of the particle or vice versa, or it may start in certain domains dispersed over the particle, and then spread. Matysik and co‐workers tried to answer this question for the transformation of a silica gel, LiChrospher, which possesses a broad pore size distribution between 10 and 50 nm, to the well‐ordered MCM‐41 exhibiting hexagonally arranged pores with a very narrow pore size distribution of ≈4 nm.…”
Section: Recent Applicationsmentioning
confidence: 99%
“…Consequently, the mechanism of the transformation and, thus, the transport properties of the intermediate transformation stages are different from the transformation of a silica gel, occurring via distinct domains. These varieties might be due to the differences in the pore size of the starting material and, hence, the ability to accommodate the newly generated MCM-41 system …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the pseudomorphic transformation can be used to generate second homogeneous mesopores in CPG (pure silica phase). [18,[20][21][22] On the contrary,the effect of pseudomorphict ransformation on the organosilica phase and the difference in the reactionk inetics between silica and organosilica phases are not well known. Therefore, we aimt oi nvestigate the influenceo fp seudomorphic transformation on the organosilica phase and to explore the feasibility of improving the porosity features of organosilica/CPG hybrid materials by pseudomorphict ransformation.…”
Section: Pseudomorphic Transformation Of Impregnated Cpgmentioning
confidence: 99%
“…[17][18][19] In the case of mesoporousC PGs, the initialp ores ystem collapses during the transformation,b ut a hierarchically porous silica materialc an be generated from macroporous CPGs. [20] The mesoporesw hich are subsequently generated within the CPG pore walls are thus accessible through the macropores,a lthough swelling of the transformed materialo ccurs whichr educes the pore diameter of the initial CPG. [20,21] Furthermore, different concepts for adjustment of the transformation degree have been discussed, for example, by changing the transformation time, the pH value or the ratio of surfactant to silica, intending to preservet he initial pore system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation